Caracterização de isolados de Sclerotinia sclerotiorum e manejo do mofo-branco e nematoide-das-galhas utilizando indutores de resistência na cultura da soja - Zanatta, Thais Pollon (2019)
The fungus Sclerotinia sclerotiorum causes white mold, one of the main diseases of the soybean crop, due to the damage caused, as well as the difficulty of control, due to a wide range of hosts and the formation of sclerotia as survival structures. The root-knot nematode (Meloidogyne spp.) cause root system compromise, reducing the absorption of water and nutrients, interfering with the proper development of plants and consequently significant reductions in productivity. Pesticides with high toxicity and high number of protective sprays are necessary for the management of white mold and phytonematoids, which have been promoting irreversible impacts on the environment, human health and resistance acquired by pathogens. Thus, resistance inducers are an alternative for the integrated management of diseases, promoting a more sustainable agriculture, as they activate latent plant protection mechanisms. The objective of this study was to perform the morphological and pathogenic characterization of 20 isolates of Sclerotinia sclerotiorum, to evaluate the effect of resistance inducers on the management of white mold and root-knot nematode and to evaluate the protection period induced by the elicitors studied involvement of some enzymes such as phenylalanine ammonia-lyases, peroxidases and polyphenoloxidase. The experiments were conducted at the Federal University of Santa Maria, campus Frederico Westphalen/RS. Twenty isolates of Sclerotinia sclerotiorum were characterized for their morphology, evaluating characteristics as time required for the fungus to occupy the plaque; density of mycelium formed, colony coloration, mycelial growth velocity, formation of sclerotia, formation of the first sclerodium, total amount of sclerodes formed by plaque, shape, distribution in the colony and weight of sclerodes. In addition to being pathogenically characterized by the detached leaf method. In order to evaluate resistance induction in the control of white mold and root-knot nematode, the experimental design was completely randomized in a 2x9 factorial scheme, two soybean cultivars (BMX Lança IPRO and BMX Elite IPRO) and eight resistance inducers (Big Red®, Supa Silica®, Yantra®, Reforce®, Supa Cobre®, Phyto Dunger®, Kellus Imune® and Bion®) + control (untreated and inoculated plants) with six replicates. For white-mold, two isolates (LF02 and LF06) and two species nematodes (M. arenaria and M. incognita) were evaluated. In order to evaluate the effect of the application of resistance inducers on the expression of defense mechanisms, a 2x8x8 factorial experiment was used, two cultivars (BMX Lança IPRO and BMX Elite IPRO), eight leaf collection times (1, 2, 4, 6, 8, 24, 48 and 72 hours post-inducer (HPI)) and eight inducers (Big Red®, Supa Silica®, Yantra®, Reforce®, Supa Cobre®, Phyto Dunger®, Kellus Imune® and Bion®). The evaluated populations presented wide variability for the morphological and pathogenic characteristics. It was not possible to verify the existence of common groups due to the high genetic diversity. The isolates showed different levels of aggressiveness, the two being more aggressive LF02 and LF06. Most of the resistance inducers tested were efficient in controlling S. sclerotiorum and M. arenaria and M. incognita, which varied according to cultivar and growing season, reducing the symptoms of the disease in relation to the control. Bion®, Kellus Imune®, Supa Silica®, Supa Cobre® and Big Red® inducers resulted in the best control of white mold and root-knot nematode for all evaluated parameters. The Kellus Imune®, Reforce® and Phyto Dunger® inductors stand out as the best elicitors, since they provided the best increases in the activity of the phenylalanine ammonia-lyase enzymes, peroxidases and polyphenoloxidase. Because they present low toxicity to humans and because they act directly on plant metabolism and do not have any direct effect on the target organisms, these products are shown to be promising in the induction of resistance and can be indicated for the integrated management of diseases in the culture of the plant soybean.